2005
DOI: 10.1093/nar/gki554
|View full text |Cite
|
Sign up to set email alerts
|

Binding of pRNA to the N-terminal 14 amino acids of connector protein of bacteriophage phi29

Abstract: During assembly, bacterial virus phi29 utilizes a motor to insert genomic DNA into a preformed protein shell called the procapsid. The motor contains one twelve-subunit connector with a 3.6 nm central channel for DNA transportation, six viral-encoded RNA (packaging RNA or pRNA) and a protein, gp16, with unknown stoichiometry. Recent DNA-packaging models proposed that the 5-fold procapsid vertexes and 12-fold connector (or the hexameric pRNA ring) represented a symmetry mismatch enabling production of a force t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 73 publications
3
55
0
Order By: Relevance
“…The ATPase must assemble to the head; in the other phages, the large subunit of the terminase interacts directly with the connector and perhaps the head shell, whereas in 29 it is the prohead binding domain of pRNA (Fig. 6C, blue shading) that binds directly to the head, interacting with the shell protein (14) and the connector (17)(18)(19). Prohead binding thereby positions the A-helices of pRNA (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ATPase must assemble to the head; in the other phages, the large subunit of the terminase interacts directly with the connector and perhaps the head shell, whereas in 29 it is the prohead binding domain of pRNA (Fig. 6C, blue shading) that binds directly to the head, interacting with the shell protein (14) and the connector (17)(18)(19). Prohead binding thereby positions the A-helices of pRNA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1C) (16). It is a component of the prohead, making critical interactions with both the connector (17,18) and the head shell (14,19,20). Early showing the dodecameric connector (portal) in green, the pentameric pRNA ring in magenta, and the pentameric ring ATPase gp16 in blue.…”
mentioning
confidence: 99%
“…The interaction between pRNA and the connector was demonstrated by crosslinking of the two (Garver and Guo 1997). It was found that the N-terminal 14 amino acids of gp10 are essential for pRNA binding since deletion of these 14 amino acids rendered the connector incompetent for RNA binding (Xiao et al 2005) and mutation in R3K4R5 led to a similar result (Atz et al 2007). Particularly, these three positively charged amino acids (R3K4R5) are believed to be responsible for the binding to pRNA with the negatively charged phosphate backbone.…”
Section: Docking Of the Hexamer Prna Model To The Motor Connectormentioning
confidence: 99%
“…17,41 A significant novelty of the phi29 DNA-packaging motor is that the motor involves an RNA molecule, 42 named pRNA, that forms a hexameric ring [43][44][45][46] and is attached to the N terminus of the connector protein gp10. 47 Originally, it was proposed that gp3 and gp16 were non-structural DNApackaging proteins. gp3, with its smaller molecular mass, was believed to be responsible for DNA binding, and the larger subunit, gp16, which contained the A-type and B-type sequences for ATP-binding, was believed to be responsible for procapsid binding.…”
Section: Introductionmentioning
confidence: 99%